1980
DOI: 10.1007/bf01314984
|View full text |Cite
|
Sign up to set email alerts
|

A possible bovine polyomavirus

Abstract: A virus with the characteristics of a polyomavirus was isolated from tissue cultures prepared from the kidneys of a healthy new-born calf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Antibodies could also be detected in human sera originating from people who had been in close contact with cattle, for example farmers and veterinarians (Parry & Gardner, 1986). Furthermore, a STMVlike virus was isolated from bovine kidney cell cultures, cultured in the presence of foetal bovine serum (Coackley et al, 1980). Recently, several STMV-like viruses were isolated from calf kidney cell cultures originating from 18 animals born and raised at different geographic locations (Westcott et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies could also be detected in human sera originating from people who had been in close contact with cattle, for example farmers and veterinarians (Parry & Gardner, 1986). Furthermore, a STMVlike virus was isolated from bovine kidney cell cultures, cultured in the presence of foetal bovine serum (Coackley et al, 1980). Recently, several STMV-like viruses were isolated from calf kidney cell cultures originating from 18 animals born and raised at different geographic locations (Westcott et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In 1980, COACKLE¥ et al (1) reported the detection of a polyomavirus, which they called WRSV, in tissue cultures prepared from the kidneys of a healthy newborn colostrum deprived calf. The presence of the virus was discovered when eosinophilie intra-nuelear inclusions were observed in CK coverslip cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cell lines and cell cultures derived from kidney tissues from various animals, especially monkeys, have been reported to be infected with viruses belonging to the Polyomavirus genus of the Papovaviridae (4,8,15,18,25,28,32). One of these viruses, simian virus 40 (SV40), caused much concern when it was discovered in virus seed stocks and batches of polio vaccine widely used in man between the years 1955 and 1963 (26,28).…”
Section: Introductionmentioning
confidence: 99%
“…More recently a cell line (Vero) derived from kidney tissue of an African green monkey has been shown to be chronically infected with potyomavirus HD, which is identical to STh~ T (11,32). Polyomaviruses have also been found in non-primate cell cultures: in ~ pig kidney cell line PK-15 (t8) and in cells prepared from the kidneys of a newborn calf (4). Neither of these last two viruses has been fully characterised.…”
Section: Introductionmentioning
confidence: 99%